Comparison of rehabilitation outcomes for transcatheter versus surgical aortic valve replacement as redo procedure in patients with previous cardiac surgery: Evidence based on 11 observational studies. Issue 45 (12th November 2021) - Wang, Guobin; Li, Xuefeng; Zhang, Zhaojie; Dong, Jige
Abstract: Background: Currently, the number of severe aortic stenosis (AS) patients with a history of prior cardiac surgery (PCS) has increased. Both transcatheter aortic valve replacement (TAVR) and traditional surgical aortic valve replacement (sAVR) are effective therapy for AS. However, PCS increases the risk of adverse outcomes in patients undergoing aortic valve replacement. Thus, this meta-analysis was designed to comparatively evaluate the impact of PCS on clinical outcomes between TAVR and sAVR. Methods: A systematic search of PubMed, Embase, Cochrane Library, and Web of Science up to February 1, 2021 was conducted for relevant studies that comparing TAVR and sAVR for severe AS patients with a history of PCS. The primary outcome was the non-inferiority of TAVR and sAVR in mortality. The secondary outcomes were the other clinical outcomes. Two reviewers assessed trial quality and extracted the data independently. All statistical analyses were performed using the standard statistical procedures provided in Review Manager 5.2. Results: A total of 11 studies including 8852 patients were identified. The pooled results indicated that there was no difference in 30-day, and 1-year all-cause mortality between TAVR and sAVR. No significant difference was also observed in total follow-up and cardiovascular mortality between TAVR and sAVR. However, subgroup analysis revealed significantly higher 1-year all-cause mortality (OR 1.92; 95% CI 1.05–3.52; P  = .04) and total follow-up mortality (OR 2.28; 95% CI 1.09–4.77; P  = .03) in TAVR than sAVR for patients with a history of coronary artery bypass graft, aortic valve replacement, and mitral valve reconstruction. In addition, TAVR experienced higher pacemaker implantation than sAVR. However, compared with sAVR, TAVR experienced shorter length of stay (MD –3.18 days; 95% CI –4.78 to –1.57 days) and procedural time (MD –172.01 minutes; 95% CI –251.15 to –92.88) respectively. TAVR also lead to much less bleeding than sAVR. Conclusions: Our analysis shows that TAVR as a redo procedure was equal to sAVR in mortality for severe AS patients with PCS, especially coronary artery bypass graft. We agree the advantage of TAVR as a redo procedure for patients with a history of PCS. Patients receiving TAVR experienced rapid recovery, shorter operation time and less bleeding, without increasing short and long term mortality.